2008
DOI: 10.1128/jvi.01937-07
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Recombination between Human Immunodeficiency Virus Type 1 (HIV-1) and HIV-2, Two Distinct Human Lentiviruses

Abstract: Human immunodeficiency virus type 1 (HIV-1) and HIV-2 are genetically distinct viruses that each can cause AIDS. Approximately 1 million people are infected with both HIV-1 and HIV-2. Additionally, these two viruses use the same receptor and coreceptors and can therefore infect the same target cell populations. To explore potential genetic interactions, we first examined whether RNAs from HIV-1 and HIV-2 can be copackaged into the same virion. We used modified near-full-length viruses that each contained a gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 47 publications
0
40
1
Order By: Relevance
“…We have previously measured recombination betwen HIV-1 and HIV-2 using two modified genomes, each carrying a mutated green fluorescent protein (gfp) gene; recombination between the two mutated genes could reconstitute a functional gfp gene, and its expression could be measured. We found that a very small percentage (ϳ0.5%) of infected cells had a GFP ϩ phenotype (25), which is much lower than that generated between two HIV-1 or two HIV-2 viruses (ϳ7%) (5,29). In all three studies, the gfp gene was used as a target sequence for reporting recombination; thus, regardless of the sequence diversity elsewhere in the viral genomes, the target regions between the mutations in the gfp genes contain identical sequences.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We have previously measured recombination betwen HIV-1 and HIV-2 using two modified genomes, each carrying a mutated green fluorescent protein (gfp) gene; recombination between the two mutated genes could reconstitute a functional gfp gene, and its expression could be measured. We found that a very small percentage (ϳ0.5%) of infected cells had a GFP ϩ phenotype (25), which is much lower than that generated between two HIV-1 or two HIV-2 viruses (ϳ7%) (5,29). In all three studies, the gfp gene was used as a target sequence for reporting recombination; thus, regardless of the sequence diversity elsewhere in the viral genomes, the target regions between the mutations in the gfp genes contain identical sequences.…”
Section: Discussionmentioning
confidence: 94%
“…For example, despite sharing a low level of amino acid sequence identity, the Gag polyproteins from HIV-1 and HIV-2 can coassemble into the same particle and complement each other's functions to carry out infection (2). It has also been shown in a cell culture system that HIV-1 and HIV-2 can recombine and generate hybrid genomes, albeit at a rate far lower than that occurring between two HIV-1 or between two HIV-2 genomes (25). Retroviral recombination is the result of the reverse transcriptase (RT) switching between the two copackaged RNA templates during DNA synthesis.…”
mentioning
confidence: 96%
“…For example, although naturally arising recombinants have been reported for HIV-2 (206, 315, 351), as have experimental recombinants between HIV-1 and HIV-2 (217), no natural HIV-1/HIV-2 recombinants have been reported (71,210) despite high rates of dual infection (327). Reasons for this may include limited cell coinfection and differences in RNA packaging (161,217,265). Additionally, the compartmentalization of virus strains to particular organs or other isolated sites can limit effective population sizes and thus the potential for recombination (7,171,223).…”
Section: Rna Copackaging Determinants: Producer Cell Coinfectionmentioning
confidence: 98%
“…Therefore, it is not surprising that a number of recent cross-and copackaging studies have elucidated that the specificity of retroviral gRNA packaging can be manipulated by substituting dimerization and packaging sequences at the 5 ′ end of genome from genetically distinct retroviruses (Al Dhaheri et al 2009;Al Shamsi et al 2011). This has further been substantiated by the fact that heterodimers involving RNAs from two divergent retroviruses can also be packaged (Motomura et al 2008;for review, see Johnson and Telesnitsky 2010).…”
Section: Introductionmentioning
confidence: 94%